Axisymmetric deformation of compressible, nearly incompressible, and incompressible thin layers between two rigid surfaces. (April 2021) - Movchan, Alexander B.; Rebrov, Kirill R.; Rodin, Gregory J.
Abstract: Accurate asymptotic solutions are presented for axisymmetric deformation of thin layers constrained by either two rigid plates or two rigid spheres. Those solutions are developed using Saint-Venant's principle and the layer thinness as the only assumptions. The solutions are valid in the entire range of Poisson's ratios, and allow one to distinguish among compressible, nearly incompressible, and incompressible layers. That classification involves both material and geometric parameters.